Odpowiedzi

2010-03-06T14:53:36+01:00
A) x= 10-5
x= 5
b) Tu masz błąd w zadaniu. Jeśli jest
2x + 3 = 15
2x= 15-3
2x= 12/:2
x=6
A jeśli
2x-3=15
2x= 15+3
2x=18/:2
x=9
c) 5x = 23-13
5x=10/:5
x=2
d) Tu znów błąd w przykładzie. Chyba ma być tak
3x+11=41
3x=41-11
3x=30/:3
x=10
e)-x=8-2
-x=6/:-1
x=-6
f)Bład
g) -2x =11+7
-2x = 18/:-2
x= -9
h) -5x =-12-3
-5x=-15/:-5
x=3
Zad 15
a) 2(x+3)=10
2x + 6 = 10
2x=10 - 4
2x= 6/:2
x=3
b)3(x-1)+2=8
3x-3 +2=8
3x=8-2+3
3x=9/:3
x=3
c)2(13-x)-9=1
26-2x-9=1
-2x=-16/:-2
x=8
d)3(1-x)+2=-7
3-3x+2=-7
-3x=-7-3-2
-3x=-12/:-3
x=4
4 4 4
2010-03-06T14:56:10+01:00
Zad.14
a. x+5=10/-5
x=10-5
x=5
b. 2x=3=15 ?
c. 5x+13=23 /-13
5x=23-13
5x=10 /:5
x=2
d. ?
e.-x+2=8 /-2
-x= 8-2
-x=6 /:(-1)
x=-6
f. ?
g.-2x-7=11 /+7
-2x= 11+7
-2x =18 /:(-2)
x=9
h.-5x+3=-12 /-3
-5x=-12-3
-5x=-15/:(-5)
x=3
zad.15
a)2(x+3)=10
2x+6=10/-6
2x=10/:2
x=5
b)3(x-1)+2=8
3x-3+2=8
3x-1=8 /+1
3x=9/:3
x=3
c)2(13-x)-9=1
26-2x-9=1
-2x+17 =1 /-17
-2x=1-17
-2x=-16 /:(-2)
x=8
d)3(1-x)+2=-7
3-3x+2=-7
5-3x=-7/-5
-3x=-12/:(-3)
x=4
4 5 4